Soil Organic Carbon Pools as Affected by Land Use Types in Hilly Ecosystems of Manipur - Meetei, Thounaojam Thomas; Kundu, Manik Chandra; Devi, Yumnam Bijilaxmi; Kumari, Nirmala (International Journal of Bio-resource and Stress Management, 2017)
Soil organic carbon (SOC) stock is a function of climatic conditions, vegetation and soil characteristics. SOC pool is comprised of labile and recalcitrant pools with varying residence time. Labile pool of SOC is very important as it influences soil quality, soil productivity and also it has an impact on global warming. Surface soil samples were collected on February-March, 2015 from four predominant land-use systems viz., forest, grassland, cultivated (rice) land (>10 years) and jhum land (2 years) of the humid subtropical Senapati district of Manipur, India to assess the impact of these land-uses on various pools of SOC viz., total organic carbon (TOC), oxidizable organic carbon, very labile, labile, less labile and recalcitrant carbon fractions. The SOC content of forest land recorded highest (23.68 g kg-1) and that of cultivated land recorded lowest (13.13 g kg-1). The SOC stock was highest in forest land (63.47 mg ha-1) which was however statistically at par with grassland (60.33 mg ha-1) and that cultivated land was lowest (38.69 mg ha-1). Similarly highest accumulation of TOC was observed in forest (38.78 g kg-1). About 43.19% and 37.40% of the TOC in forest land and grassland occurred as very labile C suggesting that the accumulated C could easily be lost following the land use change. Contrarily, the majority of TOC of cultivated and jhum land (47.35% and 43.65% of TOC) was stabilized in the recalcitrant pool indicating more stable nature of the accumulated organic matter.